Contrasts Between Moral and Islamic Religious Education: Dilemmas and Prospects - Mohamad Ridhuan Abdullah; Sultana, Tanzima; Shaari, Azianura Hani; Shaari , Nurliana Dalila Binti (Jurnal Pendidikan Islam, 2021)
This study has compared Islamic Religious Education (IRE) and Moral Education (ME) to identify these two subjects' innate differences. This qualitative research interviewed nine schoolteachers who were selected purposefully. Eleven themes were generated from the analysis of the interviews that manifested the findings of this research. The research findings reveal that IRE and ME have differences in their core philosophical standpoints and instruction methods. Based on the research findings, we have suggested necessary modification of Lickona’s Model of Teaching Moral if it is to be implemented to the curriculum of IRE. This study is significant to the curriculum developer of IRE to ensure the readiness of IRE teachers in addressing issues and concern related to moral questions and judgments. Moreover, in the Malaysian multicultural context, where IRE and ME mostly taught by Muslim instructors without actually equipping them with necessary formal teachers’ training on teaching Moral Education, the research findings also recommend the development of necessary teachers’ training program and inform the future training programs, developers, about the exiting differences between these two subjects so that the instructors can be equipped with the necessary training to optimize the teaching and learning of both IRE and ME.